Tectonic evolution of the southern part of Central Viet Nam and the adjacent area - Phung Van Phach; Le Duc Anh (Геодинамика и тектонофизика, 2018)
Interpretations of seismic, gravity and magnetic anomalies and structural data on the coastal zone of southern part of Central Viet Nam (SCVN) and the adjacent Tertiary basins suggest several phases in the tectonic evolution of the study region since the Late Cretaceous to Quaternary. In this paper, we try to clarify the tectonic evolution of SCVN and the adjacent continental margin. The Cretaceous – Paleocene tectonic phase commenced after cessation of the West Pacific plutonic magmatic activity that produced numerous diabases and aplite dykes of mainly sub-meridian orientation. It was characterized by N–S compression and E–W extension. The geomorphology and geology ofSE Asiawere considerably changed during the Neotectonic phases caused by collision between the Indian plate and the Eurasian continent. Two tectonic phases – Early and Late Neotectonic – are separated by a regional unconformity represented by a boundary surface between below strongly deformed strata (synrift) and above less deformed formations (post-rift). The Early Neotectonic phase was related to the left-lateral movement of the Red River Fault Zone (RRFZ) and includes two tectonic sub-phases: Eocene – Oligocene (NW–SE compression), and Oligocene – Miocene (E–W compression). Activity in the Oligocene-Miocene sub-phase gave birth to rift basins in the continental margin of the SCVN. The Late Neotectonic phase began since the RRFZ stopped left-lateral movement and the East Viet Nam (orSouth China) Sea stopped spreading. The Late Neotectonic phase is also divided into two tectonic sub-phases: Late Early Miocene (sub-meridian compression), and Late Miocene – Pliocene (NE–SW compression). The Late Miocene – Pliocene sub-phase is characterized by vertical movements that caused episodic uplifting of the onland terrains, and subsidence of the offshore Phu Khanh basin. Besides, Miocene – Pliocene-Quarternary basaltic eruptions were widespread all over the southern Indosinian terrain and the continental margin.